2023
DOI: 10.3390/pr11030653
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Partial Replacement of Yeast with CO2 Gas Hydrates as Leavening Agents in Baking of Wheat Bread

Abstract: The aim of this study is to examine how CO2 gas hydrates (CO2 GH) are used in baking, notably in the creation of wheat bread, as a leavening agent. CO2 GH were produced with the use of food grade amino acids called promoters. The article emphasizes an interesting approach by using a hybrid combination of yeast and CO2 GH. The current study is based on a comparative evaluation of leavening agents in bread with (1) GH with promoters (20–70% GH) and (2) GH with promoters + yeast as a partial replacement (25–75%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It was discovered that the standard made with yeast, EW, and RF had significantly more browning than the other standard bread made only with EW and RF or the standard made with AC, EW, and RF. The reason might be attributed to the fact that yeast impacts bread color by producing secondary metabolites via several metabolic pathways via non-enzymatic chemical processes such as Maillard and caramelization [ 21 , 22 , 23 ], which generate brown colored chemicals during baking [ 24 , 25 , 26 ]. Moreover, it was found that the addition of 40% GH in the wheat bread along with gelling agents AC, EW, and RF further enhanced the physical appearance of the bread in comparison to the standards that were made alone with EW and RF or AC, EW, and RF combinations ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was discovered that the standard made with yeast, EW, and RF had significantly more browning than the other standard bread made only with EW and RF or the standard made with AC, EW, and RF. The reason might be attributed to the fact that yeast impacts bread color by producing secondary metabolites via several metabolic pathways via non-enzymatic chemical processes such as Maillard and caramelization [ 21 , 22 , 23 ], which generate brown colored chemicals during baking [ 24 , 25 , 26 ]. Moreover, it was found that the addition of 40% GH in the wheat bread along with gelling agents AC, EW, and RF further enhanced the physical appearance of the bread in comparison to the standards that were made alone with EW and RF or AC, EW, and RF combinations ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The CO 2 GH was created in a reactor installed at the Department of Process Analytics and Cereal Science, University of Hohenheim, Stuttgart, Germany, in conjunction with installation help from the Institute of Fluid Mechanics (LSTME), FAU Erlangen, Germany [ 3 , 21 , 22 ]. The CO 2 GH was created by pouring 500 mL of distilled water mixed with natural amino acids as promoters into the reactor vessel, which was connected to the CO 2 gas cylinder at a pressure of 37 bars and a temperature of 273.15 K. After the gas molecules have been dissolved at a low temperature, the GH synthesis begins with nucleation and lasts three hours [ 3 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation